Single-cell copy number variant detection reveals the dynamics and diversity of adaptation - Lauer, Stephanie; Avecilla, Grace; Spealman, Pieter; Sethia, Gunjan; Brandt, Nathan; Levy, Sasha F.; Gresham, David (PLOS Biology, 2018)
A fluorescent reporter system reveals that copy number variants (CNVs) are repeatedly generated and selected during the early stages of adaptive evolution, resulting in initially predictable dynamics with thousands of independent CNV-containing lineages competing within populations.